Elucidation of the nitrogen-transformation mechanism for nitrite removal using a microbial-mediated iron redox cycling system. (February 2020) - Lu, Yongsheng; Huang, Xueer; Xu, Lu; Chen, Xueping; Zhou, Jizhi; Qian, Guangren; Fang, Feng
Highlights: Abiotic and biotic reductions of nitrite worked together. Abiotic reduction with biogenic Fe(II) was the sole process to produce N2 O. Amount of N2 O was depended on the types of iron oxides. Excellent cycling stability of iron oxides was observed. Abstract: Given the abundance of iron on the Earth, nitrogen-contaminated water is a key region for the biogeochemical cycling of N and Fe under anaerobic conditions. However, the biogeochemical processes between N and Fe remain uncertain, as do the understanding of nitrogen-transformation pathways. In this study, the nitrogen balance for the nitrite removal process in the system containing Shewanella oneidensis MR-1 and the iron oxide of either ferrihydrite or magnetite was elucidated by microbially mediated biotic and abiotic reactions with the participation of Fe. Gas chromatography results showed that during the subsequent operation phase with the re-addition of nitrite, nitrite reduction by biogenic Fe(II) was the sole process to produce gaseous nitrogen (N2 O), and yields of which were achieved to 65.56 % and 23.13 % with the ferrihydrite and magnetite systems, respectively. Meanwhile, both ferrihydrite and magnetite remained relatively stable with a small amount of phosphosiderite. Accompanied with biogenic Fe(II) formation in the start-up phase, reduction of nitrite to ammonia coupled with lactate oxidation could be driven by Shewanella oneidensis MR-1. Thus, in order to remediate nitrogen pollution in aquatic environment, given the intimate association between the microbial-mediated Fe mineralization process and the biogeochemical cycling of N, it is essential to truly understand the nitrogen-transformation mechanism under the coexistence of both processes.